A CeO2-matrical enhancing ECL sensing platform based on the Bi2S3-labeled inverted quenching mechanism for PSA detection. Issue 17 (19th April 2016) - Zhao, Yongbei; Wang, Qi; Li, Jianxiu; Ma, Hongmin; Zhang, Yong; Wu, Dan; Du, Bin; Wei, Qin
Abstract : A novel sandwich NH2 -Gr/Au@CeO2 -matrical enhancing ECL sensing platform was developed based on the Bi2 S3 -labeled inverted quenching mechanism for PSA detection. Abstract : In this paper, amidogen graphene (NH2 -Gr) and Au nanoparticle (NP) functionalized cerium oxide (CeO2 ) NPs (NH2 -Gr/Au@CeO2 ) have been synthesized. The prepared NH2 -Gr/Au@CeO2 exhibits strong electrochemiluminescence (ECL) activity which could be quenched efficiently by bismuth sulfide (Bi2 S3 ). Based on this principle, a novel sandwich ECL immunosensor was constructed for the detection of prostate specific antigen (PSA). NH2 -Gr was used as a loading matrix for CeO2 NPs because of its superior conductivity and a large surface area. Au NPs were used to combine anti-PSA 1 (Ab1 ) to CeO2 via the Au–NH2 covalent bond and meanwhile to enhance the sensitivity of the immunosensor. NH2 -Gr/Au@CeO2 was used as the ECL response layer. Ag NP functionalized Bi2 S3 was used to label the secondary antibody (Ab2 ). After a sandwich-type immunoreaction, a remarkable decrease of the ECL signal was observed. The signal-off sensor showed a wide linear range response from 1 pg mL −1 to 10 ng mL −1 with a low detection limit (LOD) of 0.3 pg mL −1 . The applicability of the proposed ECL immunosensor was evaluated by detecting PSA in human serum samples.